2018
DOI: 10.1016/j.solener.2018.06.103
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic forecasting of solar power, electricity consumption and net load: Investigating the effect of seasons, aggregation and penetration on prediction intervals

Abstract: This paper presents a study into the effect of aggregation of customers and an increasing share of photovoltaic (PV) power in the net load on prediction intervals (PIs) of probabilistic forecasting methods applied to distribution grid customers during winter and spring. These seasons are shown to represent challenging cases due to the increased variability of electricity consumption during winter and the increased variability in PV power production during spring. We employ a dynamic Gaussian process (GP) and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…More specifically, the choice of a temporal data granularity (data sampling frequency) for specifying consumption load profile features has a crucial impact on the results of any action or assessment, as discussed in the literature [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], see Table 1 . This table summarizes for each potential action or assessment the time resolution (data granularity) and time horizon (time slice) envisaged for the works related to load profiles in households.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, the choice of a temporal data granularity (data sampling frequency) for specifying consumption load profile features has a crucial impact on the results of any action or assessment, as discussed in the literature [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], see Table 1 . This table summarizes for each potential action or assessment the time resolution (data granularity) and time horizon (time slice) envisaged for the works related to load profiles in households.…”
Section: Introductionmentioning
confidence: 99%
“…Hoevenaars [ 64 ] showed that using a 1-h time step hid the load variability within the hour for models of renewable power systems. Regarding optimization purposes, Van der Meer [ 42 ] concluded that a 5-min time resolution provided a good balance between accuracy and the burden of data size, whereas [ 45 ] showed that using hourly data led to large biases compared to 1-min data. However, coarser data could be sufficient for household aggregation [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A nonparametric approach to obtain the density forecast is presented in [10]. The effect of the aggregation of time series of electricity load and the increasing share of PV power in the net load is evaluated in [11] by means of prediction intervals (PIs) in local electricity distribution grids.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the length of the time period, from the perspective of the data structure, the input of the prediction model is a time series of the power load. In fact, besides the previous situation, the power load is also related to many factors such as seasons, meteorological conditions and people's living habits [3,4]. In order to improve the forecasting accuracy of load, the influence of these factors must be considered.…”
Section: Introductionmentioning
confidence: 99%